2017
DOI: 10.2319/061217-388.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flapless osteoperforation-assisted tooth movement on atrophic alveolar ridge: Histomorphometric and gene-enrichment analysis

Abstract: Objective: To investigate the effect of flapless osteoperforation on the tissue response of the atrophic alveolar ridge affected by orthodontic tooth movement (OTM). Materials and Methods: An atrophic alveolar ridge model was established in the mandibular quadrants of eight beagle dogs. As a split-mouth design, the quadrants were randomly divided into group C (OTM only) and group OP (OTM with flapless osteoperforation). The rate of OTM for 10 weeks was compared between groups, and micro-CT-based histomorphomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Some studies have demonstrated that MOP is a safe method 8 that may facilitate root movement, 16 induce cellular activity, and accelerate tooth movement 8 , 17 , 18 without causing bacteremia. 19 Flapless osteoperforations have been reported to increase the rate of orthodontic tooth movement toward the atrophic ridge, while maintaining a low bone density 20 and without an increased risk of root resorption. As a minimally invasive, flapless surgical intervention, MOP using miniscrews improve patient acceptance and reduce surgical risks.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that MOP is a safe method 8 that may facilitate root movement, 16 induce cellular activity, and accelerate tooth movement 8 , 17 , 18 without causing bacteremia. 19 Flapless osteoperforations have been reported to increase the rate of orthodontic tooth movement toward the atrophic ridge, while maintaining a low bone density 20 and without an increased risk of root resorption. As a minimally invasive, flapless surgical intervention, MOP using miniscrews improve patient acceptance and reduce surgical risks.…”
Section: Discussionmentioning
confidence: 99%
“…This minor surgical procedure was first introduced by Teixeira et al [6], who hypothesized that limited cortical bone perforations were sufficient to elicit RAP, hence accelerating OTM. Nevertheless, later experimental studies [7–10] have shown conflicting evidence regarding its acceleratory effect.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first well-designed RCT to investigate the effectiveness of MI-facilitated MOPs in accelerating mandibular anterior teeth alignment along with patient's pain and satisfaction. [56789] Marginal alveolar bone height loss and volumetric root resorption which has not been assessed in any of the previous studies was also assessed in our study using CBCT.…”
Section: Introductionmentioning
confidence: 99%